Words lead to deeds: Towards an organizational emergence vocabulary - Gartner, William B. (Journal of Business Venturing, 1993)
The words we use to talk about entrepreneurship influence our ability to think about this phenomenon, and subsequent to these thoughts, direct our actions towards research that might be conducted on this topic. This paper offers some words to be included in a lexicon on organizational emergence: being, circumstance, emerge, emergence, emergency, emergent evolution, equivocal, found, founder, genesis, and variation. These words are discussed and directions for research on organizational emergence are offered.